2016
DOI: 10.1590/1807-57622015.0611
|View full text |Cite
|
Sign up to set email alerts
|

O cuidado à saúde na perspectiva de trabalhadores homens portadores de doenças crônicas

Abstract: O estudo, de natureza qualitativa, buscou conhecer de que forma trabalhadores homens, com pouca escolaridade, hipertensos e diabéticos, acompanhados num serviço da rede básica de Campinas-SP, Brasil, relacionam-se com sua condição de saúde e tratamento, no intuito de contribuir com a atenção básica no (re)conhecimento das necessidades de cuidado desses usuários. A partir de relatos colhidos por meio de entrevistas semiestruturadas, foram analisados os atributos da masculinidade e a experiência do cuidado da do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
22

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
1
15
0
22
Order By: Relevance
“…However, it was noted in this study that health education is very much based on the lifestyle issues of people with NCDs, emphasizing healthy eating and the use of uninterrupted medications. It is known that these individuals need a continuous follow-up in PHC, since their situation demands changes in behavioral habits (24) .…”
Section: Discussionmentioning
confidence: 99%
“…However, it was noted in this study that health education is very much based on the lifestyle issues of people with NCDs, emphasizing healthy eating and the use of uninterrupted medications. It is known that these individuals need a continuous follow-up in PHC, since their situation demands changes in behavioral habits (24) .…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that, for the expressive number of respondents, the health team professionals did not offer solutions of care that are adequate to their realities, which occurs mainly in the North region (2) . When the offers of care are not consistent or are distant from the context of the person seeking care, a negative impact is observed in the resoluteness of care (21) . There are also difficulties to bring the practice closer to reality both in the training and in the permanent education of professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to know people closely, their life context, their potentiality and adversity, so that it is possible to maintain a relationship between professional and population that encourages empowerment. 73 With this differentiated look it is possible to work with people with CNTDs and not for them, showing them mechanisms that go beyond the prescription for treating their health condition. It is necessary to work on actions that go against the biomedical paradigm still prevailing in professional practice, which overestimates the curative aspect, and no longer responds to the effective needs of people with CNTDs.…”
Section: /18mentioning
confidence: 99%